2018
DOI: 10.3389/fpls.2018.00454
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Cell Wall Composition and Modifications During the Development of the Gynoecium Medial Domain in Arabidopsis

Abstract: In Arabidopsis, the gynoecium, the inner whorl of the flower, is the female reproductive part. Many tissues important for fertilization such as the stigma, style, transmitting tract, placenta, ovules, and septum, comprising the medial domain, arise from the carpel margin meristem. During gynoecium development, septum fusion occurs and tissues form continuously to prepare for a successful pollination and fertilization. During gynoecium development, cell wall modifications take place and one of the most importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 59 publications
0
34
0
Order By: Relevance
“…Changes in pectin methylesterification occur in tomato, apple, and strawberry fruits during ripening; pectin methylesterification is also critical for proper seed development and germination [29,30], or root development [31,32]. The most abundant polysaccharides of the secondary CW are mannans, which play a key role for proper gynoecium, i.e., fruit transition [33,34].…”
Section: Plant Cell Wall Modifications Are Coordinated To Developmentmentioning
confidence: 99%
“…Changes in pectin methylesterification occur in tomato, apple, and strawberry fruits during ripening; pectin methylesterification is also critical for proper seed development and germination [29,30], or root development [31,32]. The most abundant polysaccharides of the secondary CW are mannans, which play a key role for proper gynoecium, i.e., fruit transition [33,34].…”
Section: Plant Cell Wall Modifications Are Coordinated To Developmentmentioning
confidence: 99%
“…Our findings suggest that these two processes are altered in septum cells of the ntt stk mutant. We have recently shown that global changes in cell wall composition take place during gynoecium development (Herrera-Ubaldo and de Folter, 2018), for instance mannan polysaccharide content decreases when the gynoecium matures. Here, mannan polysaccharide content in mutant and wild-type gynoecia was analyzed; an evident alteration in mannan accumulation was observed in the medial region of the single and double mutants, suggesting that the reduction in expression of the mannanase gene AT3G26140 observed by in situ hybridization and qRT-PCR could be related to the increase in mannan accumulation.…”
Section: Co-expression Network To Identify Target Genesmentioning
confidence: 99%
“…Sections (12-15 ”m) were obtained on a rotary microtome (Reichert-Jung 2040; Leica). Tissue sections were stained with a solution of 0.5% Alcian Blue and counterstained with 0.5% Neutral Red as previously described (ZĂșñiga-Mayo et al, 2012), or with Toluidine Blue as previously described (Herrera-Ubaldo and de Folter, 2018). NTT::GUS and STK::GUS inflorescences were collected and stained as previously described (Marsch-MartĂ­nez et al, 2014).…”
Section: Histology and Microscopy Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the topics which started to be tackled recently [ 36 , 37 ] and that will be surely further explored is the possible role of the TT regulators in affecting gene expression patterns of TT cell wall polysaccharides [ 73 ], since cell wall remodeling plays an essential role during PT growth along this tissue, being directly related to its nutritional, supportive, and guiding roles.…”
Section: Key To the Highway: Pollen–pistil Interactions In The Ttmentioning
confidence: 99%